2010
DOI: 10.1130/g30427.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of low-flux intraplate volcanic fields—Basin and Range (North America) and northwest Pacific Ocean

Abstract: We compare two intraplate, Pliocene-Pleistocene volcanic fi elds in different tectonic settings-the central Basin and Range and the northwest Pacifi c Ocean. Both fi elds are characterized by widely scattered, small-volume, alkali basaltic volcanoes; within the fi elds, each volcano apparently originates from a separate, volatile-enriched parental melt from the upper mantle. There is no evidence at either fi eld for locally anomalous heat fl ow or ongoing introduction of new fl uids into the upper mantle such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 20 publications
2
78
0
Order By: Relevance
“…The WPB's volcanic fields are relatively welldescribed from a physical volcanology point of view. However, new globally significant research has recently identified the following as the critical parameters that strongly influencing the basic characteristics of the resulting volcanic fields: the interplay between the external and internal forcing of the eruption styles of small-volume mafic volcanoes; the influence of long term environmental changes on the variations of the dominant eruption styles in the evolution of the volcanic field; and the long term fluctuation of magmatic flux and output rates (Valentine & Perry, 2006;Valentine & Keating, 2007;Valentine & Perry, 2007;Keating et al, 2008;Brenna et al, 2010;Genareau et al, 2010;Valentine & Hirano, 2010;Brenna et al, 2011). An application of these new results for WPB volcanism could lead to a better understanding of the eruption history of the individual monogenetic volcanoes of WPB and could allow them to be comparedto similar volcanoes worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The WPB's volcanic fields are relatively welldescribed from a physical volcanology point of view. However, new globally significant research has recently identified the following as the critical parameters that strongly influencing the basic characteristics of the resulting volcanic fields: the interplay between the external and internal forcing of the eruption styles of small-volume mafic volcanoes; the influence of long term environmental changes on the variations of the dominant eruption styles in the evolution of the volcanic field; and the long term fluctuation of magmatic flux and output rates (Valentine & Perry, 2006;Valentine & Keating, 2007;Valentine & Perry, 2007;Keating et al, 2008;Brenna et al, 2010;Genareau et al, 2010;Valentine & Hirano, 2010;Brenna et al, 2011). An application of these new results for WPB volcanism could lead to a better understanding of the eruption history of the individual monogenetic volcanoes of WPB and could allow them to be comparedto similar volcanoes worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread occurrence of this process is indicated by the discovery of small volcanoes petit-spots across broad regions of the NW Pacific plate and near the Tonga Trench, and is supported by a reinterpretation of the origin of alkaline basalts found within accretionary prisms. This paper provides new insights into the findings of Valentine andHirano, 2010 Baba et al, 2007b;Shito et al, 2008Obayashi et al, 2006Machida et al, 2009Hirano et al, 2006Abe et al, 2006, Grégoire et al, 2000Neumann et al, 2004 …”
mentioning
confidence: 70%
“…These volcanoes comprise abundant alkaline igneous rocks that result from lower degrees of partial melting at greater depth compared to the production of tholeiitic volcanism. The formation of intraplate seamounts can be due to local melting anomalies or "hotspots" that underlie the lithosphere, plate cracking allowing preexisting melt in the upper mantle to rise to the surface (e.g., Natland and Winterer, 2005;Valentine and Hirano, 2010), or localized mantle upwelling in the shallow asthenosphere (e.g., Geldmacher et al, 2008). Hotspot volcanism is commonly associated with the presence of mantle plumes that bring hot, and thus buoyant, fertile mantle from a thermal boundary layer, such as the core-mantle or upper-lower mantle boundary, to the base of the lithosphere where the mantle melts.…”
Section: Originsmentioning
confidence: 99%
“…The most prominent and thus well-known example of hotspot/plume volcanism is the Hawaiian-Emperor island/seamount chain, where seamounts become progressively older with increasing distance from the active volcanoes forming the Hawaiian Islands (Clague and Dalrymple, 1987). Seamounts can also form along cracks resulting from stress in the oceanic lithosphere, e.g., as a result of plate cooling, plate bending outboard of subduction zones, collision of continental blocks, or abrupt changes in plate motions (Natland and Winterer, 2005;Valentine and Hirano, 2010). Petitspot volcanoes near Japan and Pliocene volcanism on Christmas Island near Indonesia, for example, formed outboard of subduction zones due to plate bending (Hirano et al, 2006;Hoernle et al, 2011).…”
mentioning
confidence: 99%